2020
DOI: 10.1136/jitc-2019-000501
|View full text |Cite
|
Sign up to set email alerts
|

Identification of FABP5 as an immunometabolic marker in human hepatocellular carcinoma

Abstract: BackgroundRegulating T-cell metabolism is crucial for their anticancer activity. Therefore, understanding the function and metabolism of human tumor-infiltrating T cells is of broad interest and clinical importance.MethodsCD3+CD45+ T cells were sorted from adjacent area or tumor core of human hepatocellular carcinoma (HCC), then the clusters and heterogeneity of T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…The oncogenic properties of FFAs transporters have been reported in diverse cancers, including hepatocellular, breast and ovarian cancer. 48–50 However, contrary or contradictory results have been reported, 51 indicating that they have a context-specific role in malignant progression. Consequently, we exclusively sought to determine the functions of FFAs transporters in the TAME.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The oncogenic properties of FFAs transporters have been reported in diverse cancers, including hepatocellular, breast and ovarian cancer. 48–50 However, contrary or contradictory results have been reported, 51 indicating that they have a context-specific role in malignant progression. Consequently, we exclusively sought to determine the functions of FFAs transporters in the TAME.…”
Section: Discussionmentioning
confidence: 98%
“… 5 , 53–55 Additionally, FFAs carried by these transporters could perturb mitochondrial metabolism to promote naïve T-cell apoptosis, inhibit anti-tumor cytokine secretion and stimulate T cell exhaustion. 48 , 56 Thus, upregulation of these FFAs transporters may accommodate malignant cells to FFAs-enriched TAMEs and formulate an immunosuppressive microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that FABP5 can reprogram lipid metabolism and promote progression and metastasis in tumors ( 74 76 ). Furthermore, FABP5 has been shown to act as a critical regulator of immune cells in microenvironments via lipid metabolism, including the protection of tissue-resident memory T cells ( 77 ), the induction of suppressive T regulatory cells ( 67 , 78 ), the maintenance of T lymphocyte homeostasis ( 79 ), the production of tolerogenic plasmacytoid dendritic cells ( 78 ), and macrophage polarization, and has also been identified as a prognostic immune-metabolic marker ( 80 , 81 ). Similarly, we identified the immunomodulatory effect of FABP5 during the differentiation of decidual PMN-MDSCs.…”
Section: Discussionmentioning
confidence: 99%
“…FABP5 is the most characterized FABP isoform in cancers. Increased FABP5 expression has been reported in hepatocellular carcinoma, cholangiocarcinoma, and liver, pancreatic, cervical, and breast cancers [96][97][98][99][100]. FABPs are rapidly emerging as essential proteins in fatty acid transport and metabolism in cancer cells.…”
Section: Mechanisms Of Fatty Acid Metabolic Reprogrammingmentioning
confidence: 99%